Estimating Potential Output in Chile : A Multivariate Filter for Mining and Non-Mining Sectors - Blagrave, Patrick (IMF Working Papers; Working Paper ;, 2016)
Using a multivariate filter, we estimate potential growth rates in Chile's mining and non-mining sectors. Estimates for the mining sector incorporate information on copper prices, whereas estimates for non-mining reflect information on inflation and unemployment rates. To better understand the drivers of potential growth, we decompose estimates into capital, labor (adjusted for human-capital and hours worked), and total-factor productivity using a production-function. Our estimates of potential output in Chile suggest that an important part of the recent growth slowdown has been structural, with potential-output growth slowing to 2 1\2 percent in recent years, although it plausibly could be higher in the medium-term.